2016
DOI: 10.1590/1807-1929/agriambi.v20n2p188-192
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a variable-rate distribution system for simultaneous fertilizer application

Abstract: A B S T R A C TThe objective of this study was to evaluate the performance of a variable-rate fertilizer distribution system for coffee crop, simultaneously applying two products. Two types of tests were performed: transversal deposition and longitudinal deposition. The transversal deposition test, with tarps, aimed to quantify the variations between programmed and applied doses, using a completely randomized design (CRD), in a factorial scheme, and the Scott-Knott test at p < 0.05. The longitudinal deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Kim et al (2008) evaluated the fertilizer flow of a granulated fertilizer pneumatic applicator and showed that for the granulated fertilizer formula 22-12-12, the coefficients of variation ranged from 6% to 11%. Barros et al (2016) evaluated the performance of a variable-rate fertilizer distribution system for coffee crops. Two types of tests were performed: transverse deposition and longitudinal deposition.…”
Section: Fertilizersmentioning
confidence: 99%
“…Kim et al (2008) evaluated the fertilizer flow of a granulated fertilizer pneumatic applicator and showed that for the granulated fertilizer formula 22-12-12, the coefficients of variation ranged from 6% to 11%. Barros et al (2016) evaluated the performance of a variable-rate fertilizer distribution system for coffee crops. Two types of tests were performed: transverse deposition and longitudinal deposition.…”
Section: Fertilizersmentioning
confidence: 99%
“…The machine for fertilizer and soil correctives application is composed by a regular fertilizer spreader and an electronic system, which enables the application of products at variable rates (Barros et al, 2016). The machine had a load volume of 1.2 m 3 , a length of 3.36 m, a height of 1.40 m, a gauge of 1.24 m and a total width of 2.15 m, including the deflectors.…”
Section: Methodsmentioning
confidence: 99%
“…The machine evaluated was a spreader for the distribution of fertilizers and soil correctives, equipped with a VRA system adapted by Barros et al (2016) [13]. The spreader had a load volume of 1.2 m 3 , with a length of 3.36 m, a height of 1.40 m and a total width 2.15 m including deflectors.…”
Section: Machinery Set Specificationmentioning
confidence: 99%
“…Studies have been performed with the aim of developing and evaluating equipment for VRA but in the scope of coffee production there are very few studies on this subject [9,13]. As these studies followed ISO 5690/1 guidelines, the caveats presented above were not considered.…”
Section: Introductionmentioning
confidence: 99%